Designing a model of academic adjustment based on educational engagement, the mediatory role of academic buoyancy in students of secondary school in Yazd province - Pouya Heydari; Alireza Manzari Tavakoli; Hamdollah Manzari Tavakoli; Amanallah Soltani (مجله علوم روانشناختی)
Background: The most important concern in today's schools is academic incompatibility. ‌ Misbehavior and incompatibility of students affect the entire learning process. The problem is that the relationships of various variables with academic adjustment have been confirmed, but the relationships of variables such as educational engagement and academic buoyancy have been neglected in the form of structural relationships, and there is a major research gap in this field. Aims: Designing a model of academic adjustment based on academic engagement, The mediatory role of academic buoyancy in students of secondary school in Yazd province. Methods: The method of the present research was applied in terms of purpose and correlational in terms of the nature of the data. The statistical population of the present study included all students of the second year of high school in Yazd province in the academic year of 1401-1402.Through multi-stage sample sampling, 420 students (223 boys and 197 girls) were selected from secondary school students in Yazd province. To measure research variables, Fredericks, Blumenfeld and Paris's educational engagement (2004), Sinha and singh's academic adjustment (1993), Martin and Marsh's academic buoyancy (2008) were used. In order to investigate the relationship between variables, Pearson correlation test was used to investigate the variable prediction dependent on the independent variable and the intermediate role of the structural model test by path analysis method in the bootstrap test. Analysis of the research data was done through structural equation modeling with SPSS24 and AMOS22 software. Results: The results of structural equation modeling showed that the final model has a good fit. The findings of the present study showed that educational engagement with the standard coefficient of 0/28 has been able to predict the students' academic adjustment positively at the meaningful level of 0/01, the educational engagement with the standard coefficient of 0/26 has been able to predict the students' academic adjustment positively measure at the meaningful level of 0/01, and academic buoyancy with standard coefficient 0/47 has been able to predict students' academic adjustment positively at a meaningful level 0/01, as well as educational engagement through the mediating role of academic buoyancy on academic adjustment to the coefficient 0/12 positively with the index (VAF= 0/30) has indirectly affected the meaning level of 0/01. Conclusion: The results of this research can provide useful information for teachers, academic advisors and educational officials and researchers in the field of academic adaptation and reducing students' educational problems. Considering that educational engagement and academic buoyancy are a strong prediction of academic adjustment. Therefore, it is possible to cope with academic incompatibility with increasing students' educational engagement and academic buoyancy and increase students' academic adjustment in schools.